A Study of the Film Adaptations of Marek Hłasko's Prose by the Students of the Film School in Łódź - Bucknall-Hołyńska, Justyna (Wydawnictwo Naukowe UAM w Poznaniu; Wydawnictwo PWSFTViT w Łodzi, 2012)
The works of Marek Hłasko have proved a reliable source of content and inspiration in Polish culture from the time of their writing to the current day, and this is demonstrated by the number of film adaptations of his literature. This article will look at Hłasko’s short stories that were written while the author lived in Poland and are collected in the book The First Step in the Clouds published in 1956. It will consider the subject matter and themes of the text, overview some examples of adaptations made by the students of the celebrated Łódź Film School, reflect as to how these have remained faithful or deviated from Hłasko’s original works, before concluding as to the reasons why the students may have been drawn to this particular source.

Opowiadania Marka Hłaski stanowią od czasu ich powstania po dziś niewyczerpane źródło tematów i inspiracji dla wielu polskich twórców, w tym studentów Szkoły Filmowej w Łodzi. Forma oraz filmowość literackich nowel zawartych w tomie Pierwszy krok w chmurach opublikowanym w 1956 r. dawała im (i wciąż daje) materiał i szansę na interesującą etiudę szkolną. I tak, przez wiele lat powstało ponad dwadzieścia ekranizacji młodych adeptów sztuki filmowej. W artykule zostaje przedstawiona ich tematyka, treść, a także sposób interpretacji prozy jednego z najciekawszych pisarzy polskich minionego stulecia.
Proza Marka Hłaski w etiudach studenckich łódzkiej Szkoły Filmowej
Justyna Bucknall-Hołyńska, Zakład Wiedzy o Kulturze Instytutu Polonistyki i Kulturoznawstwa Uniwersytetu Szczecińskiego A Study of the Film Adaptations of Marek Hłasko's Prose by the Students of the Film School in Łódź, Proza Marka Hłaski w etiudach studenckich łódzkiej Szkoły Filmowej „Images” 2012, vol. X: Microcosmos, red. A. Szpulak i W. Otto, nr 19, s. 15-22. ISSN 1731-450 język: angielski
Keywords: film adaptation; student's film (graduate, examination or practice films); PWSFTviT in Łódź; Marek Hłasko; First Step in the Clouds; adaptacja filmowa; etiuda studencka; PWSFTviT w Łodzi; Pierwszy krok w chmurach